Determining Marketing Performance Product Innovation and Digital Marketing - Asti Marlina; Lucky Hikmat Maulana; Hanif Zaidan Sinaga; Jihan Fadhila; Miranti (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
In the digital era, product innovation and digital marketing are vital for enhancing the marketing performance of fashion Micro, Small, and Medium Enterprises in Bogor City, where competition is intensifying. This study aims to examine the influence of product innovation and digital marketing, particularly through social media, on marketing performance. A quantitative approach with descriptive and verification methods was employed, using a questionnaire survey distributed to 65 fashion Micro, Small, and Medium Enterprises in Bogor City, selected via purposive sampling. Data were analyzed using SPSS software through multiple regression, correlation, and statistical hypothesis testing. The findings reveal that product innovation significantly enhances marketing performance by meeting consumer demands, while digital marketing, especially social media strategies, boosts brand visibility and customer engagement. Both factors collectively account for 60% of marketing performance variance, with social media playing a critical role in promoting innovative products. This study concludes that fashion Micro, Small, and Medium Enterprises must integrate innovative product designs with active social media marketing to remain competitive. These insights offer practical guidance for Micro, Small, and Medium Enterprises to optimize marketing strategies and strengthen market presence in a dynamic environment.